Key paediatric messages from the 2016 european respiratory society international congress - Grigg, J.; Balfour-Lynn, I.; Everard, M.; Hall, Graham; Karadag, B.; Priftis, K.; Roehr, C.; Rottier, B.; Midulla, F. (2017)
In this article, the Group Chairs of the Paediatric Assembly of the European Respiratory Society (ERS) highlight some of the most interesting abstracts presented at the 2016 ERS International Congress, which was held in London.